PRINCIPLES AND FUNCTIONS OF POLITICAL MANAGEMENT - Nikola Vojvodić; Mladen M. Ivić; Nataša Tofil; Veljko Vuković; Momo Komljenović (Journal of Process Management and New Technologies, 2016)
In the modern democratic society the politics is considered to be a skill of governing, that is, conquering and maintaining the political governance and the inevitable activity in all spheres of human activities. In the sense of negotiations the contemporary politics is "the maximal in the sphere of the possible", when, in a terrible struggle using arguments and other democratic means, one comes from the maximalistic request to the solution acceptable for both sides. Political activities would mean putting every political subject in the function of the efficient and economical satisfaction of the political needs and desires, aspirations and volitions of the political public. If the political scene is represented by the free market of political ideas, then there could be established the strategy of sensible and responsible managing in the political structures of the community, which is based on the previously researched and familiar expectations of the political public.